(untitled) (Teología, 2017)
At the beginning of January 1897 the young “porteño” priest Bartolomé Ayrolo visited the Córdoba area of ”Traslasierra” with the purpose of alleviating a pulmonary affliction that he suffered, since the doctor advised him to breathe for a time the comforting and healing mountain climate. On that occasion he had the opportunity to meet the “mentioned” Cura Brochero and to appreciate closely his multiple pastoral endeavors, being immediately captivated by his figure and the greatness of his priestly heart. Here the letters of this diocesan priest who visited the parish of Villa del Tránsito are transcribed; and whose reading allows us to contemplate that holy parish priest displaying all his efforts as a good shepherd. These texts complete the publication of the article by Juan Guillermo Durán in Theology 123.